Subvastus Exposure Compared to Parapatellar Approach in Navigated Sequential Bilateral Total Knee Arthroplasty (SBTKA): A Prospective Randomized Study - Jhurani, Anoop; Agarwal, Piyush; Aswal, Mukesh; Rasquinha, Chetan; Srivastava, Mudit (The Journal of Knee Surgery, 2019)
Subvastus approach preserves the quadriceps mechanism and may lead to improved early functional outcomes as compared with a parapatellar approach in primary knee arthroplasty. We performed a prospective randomized study to test the hypothesis if subvastus approach improves patient- and physician-reported outcomes in navigated sequential bilateral knee arthroplasty when compared with the standard parapatellar approach. A total of 93 patients were allotted in each group after power analysis and randomization done by computer-generated sequence: group S by subvastus approach and control group P by parapatellar approach. The patient's ability to walk without an aid, range of motion, blood loss, tourniquet time, complications, Knee Society Score (KSS), Knee Society Functional Score (KSFS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), Knee Injury and Osteoarthritis Outcome Score (KOOS), High Flexion Knee Score (HFKS), and visual analog scale (VAS) for pain were recorded preoperatively and postoperatively at 2 and 6 weeks and 3, 6, and 12 months. Final follow-up was done at 2 years. There was no statistical difference in the patient's ability to achieve a straight leg raise (p = 0.88), walk without an aid (p = 0.25), leaving pain medication (p = 0.48), and mean duration of hospital stay (p = 0.58) between both groups. There was no difference in KSS, FS, KOOS, WOMAC, HFKS, and VAS at 2 weeks and later follow-ups. There was no significant difference in range of motion or lateral retinacular release in both groups. Blood loss was significantly less in group S (p < 0.05), but there was a higher rate of proximal wound dehiscence and delayed healing in subvastus group (p = 0.03). Subvastus approach does not improve patient- and physician-reported outcome measures except blood loss in computer-navigated sequential bilateral knee arthroplasty and has an increased incidence of wound healing problems. The Level of evidence for the study is I.
Keywords: medial parapatellar; subvastus; computer navigation; functional outcomes; bilateral total knee arthroplasty